Role of donor-acceptor complexes and impurity band in stabilizing ferromagnetic order in Cu-doped SnO2 thin films - Li, Yongfeng (2013)
Our complementary magnetic and photoluminescence measurements reveal the correlation between the donor-acceptor complex and the ferromagnetic order in Cu-doped SnO2 thin films. Oxygen vacancies (VO) and Cu dopants form defect complexes of donor-acceptor pairs, and the associated spin-polarized impurity band leads to the narrowing of bandgap. Electronic structure calculations based on the first-principles method demonstrate that the Cu-VO complex has low formation energy and can stabilize the ferromagnetic coupling. Our results suggest that intrinsic defects and their complexes with dopants play a key role for establishing the ferromagnetic order in doped wide-bandgap oxides.